Family and school in republican societies: healthy dissonance (Práxis Educativa, 2020)
The relation and distinction between the formative roles played by the school and the family are not clearly presented. Today, the controversy over its specificities has gained even more intense contours with the “School without Party” movement and the respective Bills no. 867/2015 and no. 193/2016 affiliated with it. It is in order to thematize this controversy that this text is situated. Initially, the motivations and contents mobilized by both the movement and both bills are presented, and, secondly, the specificity and roles of family and school in the formation of new generations within a republican and democratic society are discussed. With this path, it is imagined that the configuration of a common human world finds in the context of school education its condition of possibility, not by the discrediting of multiple family expressions, but, conversely, as the spatiotemporal context in which this plurality can be effectively considered and equated.Keywords: Republican Education. School. Family. Movement “School without Party”.